Unequal Impact of Price Changes in Indonesia - Rulyusa Pratikto; Mohamad Ikhsan; Benedictus Raksaka Mahi (Institute for Economic and Social Research, 2015)
The main idea of this study is to determine the impact of relative inflation on poverty incidents and to investigate whether inflation inequality has occurred in Indonesia. Interesting results were found at regional level. Firstly, Jakarta had different poverty response with respect to price increases. Processed food and transportation inflation were more imperative for the poor in Jakarta. Secondly, the poor in province with low poverty figures were more prone to inflation. In general, the results show that food inflation has the major adverse impact on the poor. Moreover, we found that inflation in Indonesia has not been pro-poor.AbstrakTujuan utama dari penelitian ini adalah untuk menentukan dampak dari perubahan harga terhadap kemiskinan, serta juga untuk mengetahui apakah terjadi ketimpangan inflasi di Indonesia. Hasil yang menarik diperoleh dari analisa pada tingkat provinsi. Pertama, kemiskinan pada provinsi Jakarta memiliki karakteristik yang berbeda. Inflasi pada makanan jadi dan transportasi justru memiliki dampak yang lebih merugikan masyarakat miskin. Kedua, masyarakat miskin yang berada di provinsi dengan tingkat kemiskinan relatif rendah justru lebih sensitif terhadap inflasi. Secara umum, inflasi bahan makanan merupakan faktor terbesar dalam peningkatan kemiskinan. Selain itu, masyarakat miskin telah mengalami total inflasi yang lebih besar dibandingkan dengan masyarakat tidak miskin.Kata kunci: Kemiskinan; Inflasi; Elastisitas Harga terhadap Kemiskinan; Pro-Poor Price Index; Price Index for the PoorJEL classifications: E3; I3; O1; R2